1988
DOI: 10.1111/j.1365-2141.1988.tb02375.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional studies of cell‐mediated immunity in haemophilia and other bleeding disorders

Abstract: Defects of immunoregulation which occur in haemophilia, reflected by numerical changes in T lymphocyte subsets, have been further investigated in functional studies. Polyclonal T-cell activation by the mitogen phytohaemagglutinin (PHA) and specific stimulation by cytomegalovirus (CMV) or herpes simplex type 2 (HSV-2) in previously sensitized subjects were studied in peripheral blood lymphocyte and in T4-cell-enriched cultures. Compared with 12 controls, the responses of 11 patients (nine with haemophilia A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…The anti‐proliferative effect of pdFVIII was shown by the pdFVIII dose‐dependent inhibition of upregulation of combined S and G 2 M phases of DNA after PHA stimulation. These results are consistent with those of previous reports of reduced tritiated thymidine uptake by purified lymphocytes after stimulation in the presence of pdFVIII (Sullivan et al , 1986; Mahir et al , 1988). However the apoptosis promoting effects of pdFVIII on T lymphocytes after stimulation are novel findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The anti‐proliferative effect of pdFVIII was shown by the pdFVIII dose‐dependent inhibition of upregulation of combined S and G 2 M phases of DNA after PHA stimulation. These results are consistent with those of previous reports of reduced tritiated thymidine uptake by purified lymphocytes after stimulation in the presence of pdFVIII (Sullivan et al , 1986; Mahir et al , 1988). However the apoptosis promoting effects of pdFVIII on T lymphocytes after stimulation are novel findings.…”
Section: Discussionsupporting
confidence: 93%
“…Factor concentrates have been shown to have a variety of in vitro immunomodulatory effects . The proliferative response of lymphocytes from normal individuals incubated in vitro with phytohaemagglutinin (PHA) has been shown previously to be diminished in the presence of plasma‐derived factor VIII concentrate (pdFVIII) (Sullivan et al , 1986; Mahir et al , 1988).…”
mentioning
confidence: 99%
“…Our observation of impaired mitogen-induced proliferation of PBMC isolated from haemophilia A patients is not inconsistent with previous reports of significantly lower proliferative responses to PHA of PBMC isolated from haemophilia patients treated with cryoprecipitate and/or FVIII concentrates (Pollack et al, 1985;Mahir et al, 1988). In these previous studies, infection with HIV was excluded or considered unlikely, whereas infection with other viruses, such as cytomegalovirus or herpes simplex virus, was either documented or not excluded as a possibility (Pollack et al, 1985;Mahir et al, 1988). Our results differ, however, from a more recent report demonstrating that PBMC isolated from patients not infected with either HIV or hepatitis C virus had mitogen-induced proliferative responses comparable to controls (Evans et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
“…It is widely reported that clotting factor concentrate may be a cause of immunological abnormalities seen in haemophiliacs as it can inhibit T cell and monocyte function in vitro [Lederman et al, 1986;Ebil et al, 1987;Mahir et al, 1988;Thorpe et al, 19891. Our study found no such correlation, however, between the amount or type of concentrate used and the anti-HBs response in the patients.…”
Section: Discussionmentioning
confidence: 99%